Changing structure of rural workforce and economic activities in Assam: Ensuring wellbeing or struggle for sustenance - Tamuli, Mondira (IASSI Quarterly: Contributions To Indian Social Science)
Assam, situated in the North-Eastern region of India is fundamentally an agrarian economy where more than 70 per cent of the total work force depends an agriculture, providing more than 53 per cent of its total employment. - Reproduced
Keywords: Agriculture, Non-agriculture, Rural-labour market, employment, Assam